Pelatihan Penyusunan Laporan Keuangan Sederhana pada UMKM di Dusun Gebang Kalurahan Candirejo - Dentamara Kedathon; Rochmad Bayu Utomo (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2024)
One of the problems that is often experienced by MSME players is that they do not have a good financial system from recording transactions to reporting business finances so that business development is hampered due to unstructured and systemized financial management. Therefore, this service initiated a simple bookkeeping training program for MSMEs in Gebang Hamlet, Candirejo Village. This training is provided with the aim of enabling MSMEs in Gebang Hamlet to prepare simple financial reports so that MSMEs have proper and systemized financial reports. This training was carried out on two MSME partner subjects, namely Mbak Lina's Grocery Store and Bu Warsi's Lotek Warung. This service was carried out for approximately one month door to door. This service method consists of a preparation stage, an implementation stage, and a monitoring and evaluation stage. each partner already understands the procedures for collecting transaction data and preparing simple financial reports including inputting cash receipts and disbursements transactions, as well as preparing profit and loss financial reports.